2004
DOI: 10.1097/01.sla.0000120071.75691.1f
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Gastric Bypass in the Treatment of Morbid Obesity

Abstract: LGBP is a good surgical technique for the management of morbid obesity and has clear advantages over OGBP, such as a reduction in abdominal wall complications and a shorter hospital stay. The midterm weight loss is similar with both techniques. One inconvenience is that LGBP has a more complex learning curve than other advanced laparoscopic techniques, which may be associated with an increase in postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
132
0
31

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(169 citation statements)
references
References 18 publications
6
132
0
31
Order By: Relevance
“…Nguyen et al [7][8][9] performed a series of well-designed randomized controlled studies comparing laparoscopic and open gastric bypass. Another randomized study verified their overall results, showing that LRYGB offered the benefits of less pain, faster recovery, and shorter hospital stay without any detrimental effects on excess body weight loss [10].…”
mentioning
confidence: 60%
“…Nguyen et al [7][8][9] performed a series of well-designed randomized controlled studies comparing laparoscopic and open gastric bypass. Another randomized study verified their overall results, showing that LRYGB offered the benefits of less pain, faster recovery, and shorter hospital stay without any detrimental effects on excess body weight loss [10].…”
mentioning
confidence: 60%
“…A total number of 20 articles entered the meta-analysis models (fig. 1) [24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43]. …”
Section: Resultsmentioning
confidence: 99%
“…Westling and Gustavsson found that weight loss was unaffected by the surgical approach, but postoperative hospital stay was two days shorter after laparoscopic surgery (EL 1b [355]). Most recently, laparoscopic and open gastric bypass were compared by Lujan et al in a well-performed study (EL 1b [191]). The duration of surgery and hospital stay were shorter in the laparoscopic group.…”
Section: Surgical Access: Open Vs Laparoscopicmentioning
confidence: 99%